Influence of the Leguminosae secondary substances on the ecology and biology of Bruchidae - Stamopoulos, D.C. (ENTOMOLOGIA HELLENICA, 1987)
Secondary substances of leguminous seeds, suggest themselves to be the main defense mechanisms against Bruchidae which also develop their own mechanisms to avoid and/or detoxify these compounds. These interactions between plants and insects through the secondary substances, lead to the appearance of divergent or convergent defence mechanisms at the plant level and to the specialist or generalist at the insect one. Among the most widespread secondary compounds in the Leguminosae, are the tannins, lignins, lectins, alkaloids, enzyme inhibitors, polysaccharides, non protein amino acids, toxic glycosides and miscellaneous toxins